A Review on Catalytic Membranes Production and Applications - Heba Abdallah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The development of the chemical industry regarding reducing the production cost and obtaining a high-quality product with low environmental impact became the essential requirements of the world in these days. The catalytic membrane is considered as one of the new alternative solutions of catalysts problems in the industries, where the reaction and separation can be amalgamated in one unit. The catalytic membrane has numerous advantages such as breaking the thermodynamic equilibrium limitation, increasing conversion rate, reducing the recycle and separation costs. But the limitation or most disadvantages of catalytic membranes related to the high capital costs for fabrication or the fact that manufacturing process is still under development. This review article summarizes the most recent advances and research activities related to preparation, characterization, and applications of catalytic membranes. In this article, various types of catalytic membranes are displayed with different applications and explained the positive impacts of using catalytic membranes in various reactions.